Immunoregulation of Glia after spinal cord injury: a bibliometric analysis - Huang, Yi; Hu, Rong; Wu, Lei; He, Kelin; Ma, Ruijie (Frontiers in Immunology, 2024)
Abstract Objective: Immunoregulation is a complex and critical process in the pathological process of spinal cord injury (SCI), which is regulated by various factors and plays an important role in the functional repair of SCI. This study aimed to explore the research hotspots and trends of glial cell immunoregulation after SCI from a bibliometric perspective. Methods: Data on publications related to glial cell immunoregulation after SCI, published from 2004 to 2023, were obtained from the Web of Science Core Collection. Countries, institutions, authors, journals, and keywords in the topic were quantitatively analyzed using the R package "bibliometrix", VOSviewer, Citespace, and the Bibliometrics Online Analysis Platform. Results: A total of 613 papers were included, with an average annual growth rate of 9.39%. The papers came from 36 countries, with the United States having the highest output, initiating collaborations with 27 countries. Nantong University was the most influential institution. We identified 3,177 authors, of whom Schwartz, m, of the Weizmann Institute of Science, was ranked first regarding both field-specific H-index (18) and average number of citations per document (151.44). Glia ranked first among journals with 2,574 total citations. The keywords "microglia," "activation," "macrophages," "astrocytes," and "neuroinflammation" represented recent hot topics and are expected to remain a focus of future research. Conclusion: These findings strongly suggest that the immunomodulatory effects of microglia, astrocytes, and glial cell interactions may be critical in promoting nerve regeneration and repair after SCI. Research on the immunoregulation of glial cells after SCI is emerging, and there should be greater cooperation and communication between countries and institutions to promote the development of this field and benefit more SCI patients.